The effect of the institutional features of the Indian system of personal laws on personal religious autonomy - Ahmed, F (2008)
This thesis addresses the question of how the Indian system of personal laws ('the system') affects personal religious autonomy. It does so by considering what implications three major institutional features of the system, namely (a) the identification of individuals as members of religious groups by the state; (b) the application of personal laws ostensibly based on religious doctrine, as understood by the state, to these individuals and (c) the limited movement allowed between the different personal laws, and between a personal law and the general non-religious laws, have for the religious autonomy of those governed by the system. Several arguments in support of the system, including those that suggest that it might provide valuable recognition of the collective aspects of religious identity, support the proper functioning of religious groups and provide individuals with more options than they otherwise would have had, are considered. However the thesis concludes that contrary to what some who argue for the preservation of the system claim, it has an adverse effect on religious autonomy. It misrecognises individuals and their religious understandings, it interferes with their personal integrity and it invades their privacy. The limited movement allowed by feature (c) above does not significantly mitigate the problems with system. Concerns relating to religious autonomy, this thesis thus finds, constitute an important set of objections to the system as it now functions.